Primary education: with a review of the German, Irish, and English systems - Bailey, William F. (Statistical and Social Inquiry Society of Ireland, 1884)
In the paper which I would lay before the Statistical and Social Inquiry Society this evening, I have endeavoured to bring under consideration the more important questions which occupy the attention of statesmen and all interested in social reform with respect to the great problem of Primary Education. The urgent necessity of considering the whole subject m this country is evident from the important debate which arose in the last session of the House of Commons, on Mr. O'Shaughnessy's motion in favour of compulsory education. It seems to me that the best way of obtaining just ideas on the subject, and of improving our own system, is by viewing it in comparison with the systems of other countries, and thus judging of their relative advantages and disadvantages.
Read before the Society, 18 December 1883
Keywords: Primary education; English education system; Irish education system; German education system; 314.15